Silver in the sun - Barclay, Hilary M. ([Findon, S. Aust.] : N.C. Howard and H.M. Barclay, 1989)
Annotation pending.
Available from Mrs H. Barclay, 7 Blasscock Avenue, Findon SA 5023.
Keywords: Literature and stories - Fiction; South Australia -- History -- 1851-1891 -- Fiction